More than just location: how engineering undergraduate students choose their schools and programs - Wang, Xi; Dai, Minhao; Mathis, Robin Smith; Zhao, Tianjiao; Morgan, Ned (Frontiers in Education, 2025)
IntroductionEngineering higher education faces difficulties in attracting and enrolling motivated students in engineering programs. These challenges call for a deeper insight into the factors that influence student choice when selecting an institution and its engineering programs. Understanding these factors enables institutions to comprehend why students prefer one institution over others and leads to strategies that can enhance the overall student experience, which could ultimately increase enrollment and retention.MethodsThe current study conducted a mixed inductive and deductive content analysis of open-ended responses from a multi-institutional survey administered to undergraduate engineering students (n = 473) across nine states in the Northeastern and Midwestern United States. Students responded with their main reasons for choosing their current schools for their engineering education.ResultsThe results yielded a total of 25 factors reflecting a robust number of reasons why undergraduate engineering students chose a university/program. The most frequently mentioned factors included location, program standing, career development, athletic, institutional standing, majors, and cost. Meanwhile, factors such as religion, safety, study length, research, influences from others, and expected income were the least frequently mentioned. Results also showed that racial minority students were more likely to have institutional curriculum and tuition assistance programs, but less likely to have school size, location, and athletic programs as reasons why they chose their university/program. The results showed a similar pattern for female students. The results highlight the importance of accentuating and differentiating location in marketing strategies in engineering programs.DiscussionOur study highlights several equally influential factors, including Program standing and Career development. These call for a greater effort to establish a distinct brand image for each engineering program to promote themselves instead of leaning heavily on broader reputation and standing as a school. Institutions should tailor their promotional strategy to focus on showcasing the characteristics of individual engineering disciplines that align with a prospective student’s interests, rather than providing a general institutional standing overview. Faculty could showcase real-world projects and incorporate undergraduate research experiences into coursework, matching students’ skill levels and reflecting the practice of “meeting where students are,” ultimately shaping students’ educational paths and career trajectories.